Underestimated and ignored? The impacts of microplastic on soil invertebrates—Current scientific knowledge and research needs - Möhrke, Anne Christel Franka; Haegerbaeumer, Arne; Traunspurger, Walter; Höss, Sebastian (Frontiers in Environmental Science, 2022)
The accumulation of plastics in the environment is a major problem in the Anthropocene. As most plastic is produced, used and discarded on land, ~4-23 times more plastics are deposited in soils than in the oceans. However, there is far too little knowledge on the ecological consequences of plastic pollution, especially for soil ecosystems. Microplastics (<5 mm), whether derived from larger plastic pieces through physical, chemical and biological degradation or produced as primary particles, is of considerable interest, as they can be ingested by organisms at the basis of the trophic net and transferred to higher trophic levels. Nonetheless, although the assessment of microplastic effects on soil invertebrates is of undeniable relevance, most studies have focussed on nano- and microplastics in aquatic environments. This review examines the current state of knowledge regarding the effects of microplastics on soil invertebrates. As part of the soil biota, these organisms are of utmost importance for carbon cycling, respiration and biodiversity. Based on strict quality criteria, the data of 45 papers reporting ecotoxicological effects on soil invertebrates were analyzed, considering various test organisms and types of microplastic (in terms of polymer, shape and size). However, although different impacts were demonstrated, a deduction of general effect tendencies of microplastics in soils was difficult due to the scarcity of data and the use of diverse methodological setups. Moreover, almost all experiments were based on short-term single-species testing involving only a small number of species and single microplastic types. The review concludes with a discussion of the remaining knowledge gap and the needs for a standardized approach allowing an ecologically relevant risk assessment of the impacts of microplastic on invertebrates in terrestrial ecosystems.